Microwave Dielectric Study of Tetramethylurea and N, N-Dimethylacetamide Binary Mixture in Benzene - V. Sharma; N. Thakur (E-Journal of Chemistry)
Dielectric relaxation of the binary mixture of tetramethylurea and N, N-dimethylacetamide has been studied at fixed frequency and temperature (9.88 GHz & 298 K respectively) in benzene solution. Different dielectric parameters like the dielectric constant (ε') and the dielectric loss (ε") at microwave frequency, static dielectric constant (ε0) and dielectric constant (ε∞) at optical frequency were determined. The values of relaxation time (τ(1), τ(2), τ(0) & τGK) have been calculated using higasi’s single frequency method and Gopala Krishna’s method. Using Eyring’s rate theory, the activation energies for the process of dielectric relaxation and viscous flow were calculated and compared. The study of dielectric properties of the binary mixture reveals the existence of the solute-solute type of molecular associations.